GB20-5A8-31, an anti-TL1A antibody for treating inflammatory bowel disease - Huang, Yu; You, Qiongying; Yao, Tianqi; Tong, Yanrong; Yang, Xiaodong; Zhang, Xiangling; Huang, Xiaoting; Chen, Qin; Lu, Feng; Li, Huiming; Wang, Junfeng; Qin, Suofu (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD) remains a critical unmet medical challenge, with a substantial number of patients experiencing ineffective treatment or therapeutic failure over time. Here, GB20-5A8-31, a novel anti-TNF-like ligand 1A (TL1A) antibody, was engineered for high potency and superior developability. GB20-5A8–31 exhibited ultra-high affinity (KD = 5.11×10–11 M) for human TL1A, potent inhibition of TL1A signaling in vitro. Meanwhile, GB20-5A8–31 demonstrated potent anti-inflammatory effects and anti-fibrotic tendencies in both the 2,4,6-trinitro-benzenesulfonic acid-induced rat and dextran sulfate-induced hTLIA-transgenic mouse acute IBD models. Its favorable pharmacokinetic profile, including an extended half-life (T1/2 = 248.54 h) in hFcRn-transgenic Sprague-Dawley rats, supports sustained target engagement. Crucially, GB20-5A8–31 exhibits advantageous biophysical properties—including high stability, solubility, and low aggregation—which facilitate the development of high-concentration formulations aimed at improving patient compliance. In summary, these findings indicate that GB20-5A8–31 is a therapeutic candidate for IBD with promising preclinical efficacy and the potential to advance to the Chemistry, Manufacturing and Controls research.